E-Commerce Marketing - Kleindl, Brad; Burrow, Jim (Cincinnati, Ohio : South-Western ; London : Thomson Learning, 2004)
This profile provides the curricular framework for Ohio Tech Prep programs in e-commerce marketing beginning in high school and continuing through the end of the associate degree. It includes a comprehensive set of e-commerce marketing competencies that reflect job opportunities and skills required for e-commerce marketing professionals today and in the future. Introductory materials include an occupational area definition; key to profile codes; and state competency profile matrix. Competencies are divided into 31 units. This information is provided for each competency: whether business, industry, and labor determine the competency to be essential or recommended; grade level(s) at which technical educators feel the competency should be introduced, reinforced, or proficient; the competency number and statement; and list of competency builders. Units are e-commerce basics; marketing and business basics; economic concepts and international business; information technology basics; computer applications; Internet; programming; networking; information security; graphic design basics; digital media design; Web page design; personalization; electronic payment systems; promotion; consumer behavior; branding; integrated business systems; supply chain management; pricing; product management; customer relationship management; market research; data mining; data warehousing; marketing management; business management and entrepreneurship; financial management functions; e-commerce/business law, ethics, and legal issues; writing and documentation for marketing; and digital marketplace design. (YLB)
Administrators.
Practitioners.
Teachers.
Microfiche.
Keywords: Internet marketing; Electronic Commerce; Data Mining -- Data Warehousing -- Ohio; Guides, Non-Classroom.; Reference Materials, General